Measuring expatriate cross-cultural stress: a reanalysis of the CernySmith Assessment - Edwards, Keith J. (Journal of psychology and theology, 2016)
This study reports a statistical modification of a psychometric expatriate adjustment survey (e.g., the CernySmith Assessment or CSA) applied to expatriate missionary and humanitarian workers and their families. Earlier CSA survey items assisted in a need for rapid response clinical assessment originating from clinical observations, literature with a factor analysis resulting in 20 subscales and 5 qualitative content domains (Organizational, Cultural, Relational, Behavioral, and Personal). However, the assessment required more robust scale and factor analysis development to assure replicability. The present study analyzed 1,133 respondents working in 130 host countries. After various factor analytical iterations, a final CSA psychometric scale of 5 factors and 15 subscales (and a final 3 factor solution) emerged that compares with other known expatriate employee and spousal adjustment scales (Bhaskar-Shrinivas, Harrison, Shaffer, & Luk, 2005; Black, Mendenhall, & Oddou, 1991; Brown, 2008). This improved adjustment assessment answers Hippier, Caligiuri, and Johnson's (2014) call for robust expatriate adjustment assessments. The CSA moves adjustment measurement forward with new domains of resilience (Well-Being, Past Stresses, and Focus) and personal foundation (Spirituality, Health, and Habits). In light of 20-40% rate of preventable missionary attrition, the CSA should contribute to research, practice, and organizational support.